A low-temperature super-elastic Ti-Ni-Sn shape memory alloy and a preparation method and application thereof

CN118086724BActive Publication Date: 2026-10-27HARBIN INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410161723.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-05
Publication Date
2026-10-27
Estimated Expiration
2044-02-05

AI Technical Summary

Technical Problem

[0007]本发明针对目前缺少低温环境下超弹性形状记忆合金的技术问题,本发明提供了一种低温超弹性Ti-Ni-Sn形状记忆合金及其制备方法和应用

Benefits of technology

[0024]本发明在近等原子比二元TiNi合金中加入第三合金元素Sn,以Sn原子取代近等原子比TiNi合金中的Ti原子,由于Sn原子和Ti原子的原子尺寸不同,会产生晶格畸变,阻碍合金的马氏体相变,使材料的马氏体相变温度降低,从而获得在低温环境下具有超弹性的TiNiSn形状记忆合金材料。与此同时,本发明结合冷轧及低温退火,使合金的热致马氏体相变被强烈抑制。最终获得在-50℃以下具有低温超弹性的TiNiSn三元形状记忆合金。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118086724B_ABST
    Figure CN118086724B_ABST
Patent Text Reader

Abstract

The application discloses a low-temperature super-elastic Ti-Ni-Sn shape memory alloy as well as a preparation method and application thereof. The application belongs to the field of shape memory alloys. The application aims at the technical problem that there is a lack of super-elastic shape memory alloys under a low-temperature environment. The chemical formula of the Ti-Ni-Sn shape memory alloy is Ti 49.8‑x‑y Ni 50.2+x Sn y (x=0~0.4, y=1.5~2.5). In the application, a third alloy element Sn is added into a near-equiatomic binary TiNi alloy, Ti atoms in the near-equiatomic TiNi alloy are replaced by Sn atoms, and the martensitic phase transition temperature of the material is reduced. Meanwhile, cold rolling and low-temperature annealing are combined, and the thermal-induced martensitic phase transition of the alloy is strongly inhibited. Finally, the TiNiSn ternary shape memory alloy with low-temperature super-elasticity below-50 DEG C is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of shape memory alloys, specifically relating to a low-temperature superelastic Ti-Ni-Sn shape memory alloy, its preparation method, and its applications. Background Technology

[0002] Superelastic shape memory alloys are a class of materials that utilize stress-induced reversible thermoelastic martensitic phase transformations to achieve large recoverable deformation capabilities (TiNi alloys can achieve a fully recoverable strain of up to 8%). Compared to traditional metallic materials, their recoverable strain is much larger (the recoverable strain of traditional metallic materials is generally between 1.0% and 2.0%). Due to their unique superelasticity, shape memory alloys have attracted the attention of researchers both domestically and internationally and have been widely applied in fields such as medical superelastic guidewires.

[0003] In recent years, my country's space program has made rapid progress, with steady advancements in space station, lunar exploration, and Mars exploration missions. In space exploration missions, buffers are crucial for ensuring a soft landing of the lander on a planetary surface, protecting the lander's instruments from damage during descent. Shape memory alloys, with their large recoverable strain and significant stress hysteresis that dissipates energy, possess excellent energy-absorbing and buffering properties, making them suitable for buffer fabrication.

[0004] Although shape memory alloys have made some research progress and can basically meet the application requirements of conventional technologies, the operating temperatures of existing shape memory alloys are difficult to meet the low-temperature requirements of deep space exploration environments. The lunar surface experiences a diurnal temperature range of -170℃ to 130℃, a temperature difference of nearly 300℃; while the Martian surface experiences a diurnal temperature range of -150℃ to 20℃, a temperature difference of nearly 200℃. The austenitic phase transformation temperature (A) of TiNi shape memory alloy, which has been studied the longest and is most commercially available, is... fThe temperature range is -50℃ to 95℃. Below -50℃, the material does not exhibit superelasticity. Currently, shape memory alloys exhibiting superelasticity at low temperatures are mainly TiNi-based, Cu-based, and Fe-based. Cu-based shape memory alloys suffer from drawbacks such as high intergranular brittleness, easy fracture, and poor cycle performance, especially since high-performance Cu-based low-temperature superelastic shape memory alloys are often bamboo-like crystals or single crystals, unsuitable for large-scale production. While Fe-based shape memory alloys have low raw material costs and good toughness and plasticity, materials with excellent low-temperature superelasticity are usually single crystals. Single-crystal preparation is costly, inefficient, and unsuitable for large-size and mass production. TiNi-based shape memory alloys are the most mature of these three types and are currently widely used in pipe fittings, medical superelastic guidewires, etc. They have the advantages of simple preparation methods and the ability to mass-produce large-size materials. However, there are currently relatively few TiNi-based superelastic shape memory alloys suitable for low-temperature environments. Therefore, it is essential to enrich the variety of TiNi-based low-temperature superelastic shape memory alloys to provide more options for my country's deep space exploration.

[0005] In summary, hyperelastic shape memory alloys have attracted widespread attention from scholars both domestically and internationally due to their large recoverable strain and stress hysteresis energy absorption characteristics. Among numerous hyperelastic shape memory materials, titanium-nickel-based alloys (mainly including titanium-nickel-iron, titanium-nickel-niobium, titanium-nickel-copper, and their quaternary or pentagonal alloys) can produce large hyperelastic deformations near the primary structure phase transition temperature range and have been widely used in industrial and medical fields, such as medical guidewires, making them a class of high-performance structural functional materials. Although research on room temperature and high temperature shape memory alloys is very mature, high-performance hyperelastic shape memory alloys suitable for low-temperature environments are still lacking.

[0006] Authorization announcement number CN111411263B, entitled "A Low-Temperature Superelastic Ti-Ni-Cu-Y-Hf Shape Memory Alloy and Its Preparation Method," discloses a titanium-nickel-copper pentagonal alloy. Although the alloy's compressive superelastic recovery rate can reach 100% after training, the phase transformation temperature remains high, and the austenite transformation completion temperature (A0.05) is relatively low. f The current temperature range is still around room temperature (10-20℃), which cannot meet the requirements for superelasticity at lower temperatures. Application publication number CN103088234A, entitled "A Low-Gap Titanium-Nickel-Vanadium Shape Memory Alloy Material for Low-Temperature Superelasticity," discloses a quaternary alloy. This alloy, after aging treatment at 300℃ and 400℃ for different times, achieves a low-temperature tensile deformation of 6%, and the residual strain after unloading is less than 0.3%. However, the test temperature of this material is only -10℃, which still cannot meet the requirements for superelasticity at lower temperatures. Therefore, the development of low-temperature superelastic shape memory alloys is particularly necessary. Summary of the Invention

[0007] This invention addresses the current lack of high-elasticity shape memory alloys for low-temperature environments by providing a low-temperature high-elasticity Ti-Ni-Sn shape memory alloy, its preparation method, and its applications.

[0008] The technical solution of the present invention is as follows:

[0009] One objective of this invention is to provide a low-temperature superelastic Ti-Ni-Sn shape memory alloy, wherein the chemical formula of the Ti-Ni-Sn shape memory alloy is Ti 49.8-x-y Ni 50.2+x Sn y (Atomic percentage, x = 0–0.4, y = 1.5–2.5).

[0010] Further specify, x = 0.1, y = 2.

[0011] The second objective of this invention is to provide a method for preparing a low-temperature superelastic Ti-Ni-Sn shape memory alloy, the method comprising the following steps:

[0012] (1) Melting: Alloy ingots are prepared by vacuum arc melting according to the alloy composition;

[0013] (2) Homogenization heat treatment: The alloy ingot is subjected to homogenization heat treatment under a sealed vacuum condition;

[0014] (3) Room temperature cold rolling: Cold rolling of the homogenized heat-treated ingot at room temperature;

[0015] (4) Low-temperature annealing: The cold-rolled ingot is subjected to low-temperature annealing to obtain a Ti-Ni-Sn shape memory alloy with low-temperature superelasticity.

[0016] Further specifying, the homogenization heat treatment in step (2) is to keep at 1000-1050℃ for 24 hours.

[0017] Furthermore, when y≤2, the homogenization heat treatment temperature is 1000℃, and when y>2, the homogenization heat treatment temperature is 1050℃.

[0018] Further, in step (3), the deformation per pass is 1%, and the total deformation is 20-30%.

[0019] Furthermore, as y increases, the total deformation of cold rolling decreases.

[0020] Further specified, the annealing temperature in step (4) is 350-450℃ and the time is 20-40min.

[0021] The third objective of this invention is to provide an application of a low-temperature superelastic Ti-Ni-Sn shape memory alloy in the field of low-temperature deep space exploration.

[0022] To further define, low temperature refers to temperatures below -50°C.

[0023] The advantages of this invention compared to the prior art are:

[0024] This invention introduces a third alloying element, Sn, into a near-equal atomic ratio binary TiNi alloy. Sn atoms replace Ti atoms in the near-equal atomic ratio TiNi alloy. Due to the difference in atomic size between Sn and Ti atoms, lattice distortion occurs, hindering the martensitic phase transformation of the alloy and lowering its martensitic phase transformation temperature. This results in a TiNiSn shape memory alloy material exhibiting superelasticity at low temperatures. Simultaneously, this invention combines cold rolling and low-temperature annealing to strongly suppress the thermally induced martensitic phase transformation of the alloy. Ultimately, a TiNiSn ternary shape memory alloy exhibiting low-temperature superelasticity below -50℃ is obtained. Attached Figure Description

[0025] Figure 1 Ti after step (1) of Example 1 49.8-x-y Ni 50.2+x Sn y Microscopic morphology of the alloy (x = 0.1, y = 2);

[0026] Figure 2 Ti after step (1) of Example 1 49.8-x-y Ni 50.2+x Sn y Room temperature XRD pattern of the alloy (x = 0.1, y = 2);

[0027] Figure 3 Ti after step (1) of Example 1 49.8-x-y Ni 50.2+x Sn y Differential scanning calorimetry plot of alloy (x=0.1,y=2);

[0028] Figure 4 Ti obtained in Examples 1-2 49.8-x-y Ni 50.2+x Sn y (x = 0.1, y = 2) DSC curves of the alloy; (a) - Example 1, (b) - Example 2;

[0029] Figure 5 Ti at -80℃ and -60℃ obtained in Example 1 49.8-x-y Ni 50.2+x Sn y (x=0.1,y=2) Tensile stress-strain curves of alloys;

[0030] Figure 6 Ti at -80℃ and -60℃ obtained in Example 2 49.8-x-y Ni 50.2+x Sn y (x=0.1,y=2) Tensile stress-strain curves of alloys. Detailed Implementation

[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0032] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0033] Example 1

[0034] The preparation method of the low-temperature superelastic Ti-Ni-Sn shape memory alloy in this embodiment is carried out according to the following steps:

[0035] (1) Smelting.

[0036] First, the vacuum level in the smelting furnace is reduced to 0.5 × 10⁻⁶. -4 Pa, then high-purity argon gas (99.999%) is introduced to atmospheric pressure, and then a vacuum is drawn to 0.5 × 10⁻⁶. -4 Pa, then fill with high-purity argon gas (99.999%), and repeat the gas washing process three times.

[0037] Then press Ti 47.7 Ni 50.3 The composition of Sn2 (atomic percentage) is determined by weighing out pure metallic Sn, pure metallic Ni, and pure metallic Ti. Pure metallic Sn (99.99%), pure metallic Ni (99.99%), and pure metallic Ti (99.99%) are placed at the bottom, middle, and top of the copper crucible in order of increasing melting point to reduce the volatilization of low-melting-point elements during the smelting process. Before formal smelting, the pure Ti ingots are remelted three times to absorb any remaining oxygen in the furnace.

[0038] The Ti-Ni-Sn alloy ingot was then melted at a current of 220A. After each melting of the alloy ingot, the ingot was flipped and remelted. The melting was repeated 6 times to obtain the initial Ti-Ni-Sn alloy ingot.

[0039] (2) Homogenization heat treatment.

[0040] First, the Ti-Ni-Sn alloy ingot was cut into blocks with a height of 5mm using wire electrical discharge machining. The ingot surface was then cleaned with acetone solution in an ultrasonic cleaner for 3 minutes to remove oil stains. After removal, it was rinsed with alcohol and then dried completely with a cold air blower for 1 minute.

[0041] To prevent oxidation of the alloy ingot at high temperatures, it needs to be sealed in a vacuum-sealed quartz tube. The specific procedure is as follows: one end is sealed and the other end is open, with an inner diameter φ... ID =22mm, outer diameter φ OD A quartz tube with a diameter of 25mm and a length L0 of 250mm is prepared. The ingot to be homogenized by heat treatment is placed at one end of the sealed quartz tube, and a quartz plug is inserted for later sealing. First, a vacuum pump is used to evacuate the vacuum inside the quartz tube to <10. -6 After passing through Pa, high-purity argon gas (99.999%) is introduced for purging, and then the vacuum level inside the quartz tube is evacuated to <10. -6 Pa. A vacuum pump continuously evacuates air to maintain a constant vacuum level inside the quartz tube. A flame gun is used to heat the quartz stopper while the quartz tube is rotated to ensure uniform heating of the stopper. After melting, cooling, and solidifying, the quartz tube and stopper bond together, maintaining a high vacuum on the side where the alloy ingot is placed.

[0042] Subsequently, a homogenization heat treatment was performed by holding the tube at 1000℃ for 24 hours. After the heat treatment was completed, the quartz tube was quickly placed in water and the glass tube was broken, followed by room temperature water quenching.

[0043] (3) Room temperature cold rolling.

[0044] The homogenized heat-treated ingot is cold-rolled at room temperature (25°C) using a cold rolling mill. The deformation amount per pass is 1%, and no annealing is performed during the rolling process. Due to the springback of the material, when the roll pressure reaches the target deformation amount, the reduction in material thickness is less than the roll pressure, so rolling should continue. After each rolling pass, the material thickness is measured using vernier calipers until the ingot thickness reduction reaches 20%.

[0045] (4) Low-temperature annealing.

[0046] The cold-rolled and deformed ingot was sealed with a tube (same as in step (2)). The heat treatment process involved first heating the heat treatment furnace to 400°C, and then placing the sealed quartz tube into the furnace and holding it for 30 minutes. After the heat treatment was completed, the quartz tube was quickly placed in water and the glass tube was broken. The tube was then quenched at room temperature to obtain a low-temperature superelastic Ti-Ni-Sn shape memory alloy.

[0047] Example 2

[0048] The preparation method of the low-temperature superelastic Ti-Ni-Sn shape memory alloy in this embodiment is carried out according to the following steps:

[0049] (1) Smelting.

[0050] First, the vacuum level in the smelting furnace is reduced to 0.5 × 10⁻⁶. -4 Pa, then high-purity argon gas (99.999%) is introduced to atmospheric pressure, and then a vacuum is drawn to 0.5 × 10⁻⁶. -4 Pa, then fill with high-purity argon gas (99.999%), and repeat the gas washing process three times.

[0051] Then press Ti 47.7 Ni 50.3 The composition of Sn2 (atomic percentage) is determined by weighing out pure metallic Sn, pure metallic Ni, and pure metallic Ti. Pure metallic Sn (99.99%), pure metallic Ni (99.99%), and pure metallic Ti (99.99%) are placed at the bottom, middle, and top of the copper crucible in order of increasing melting point to reduce the volatilization of low-melting-point elements during the smelting process. Before formal smelting, the pure Ti ingots are remelted three times to absorb any remaining oxygen in the furnace.

[0052] The Ti-Ni-Sn alloy ingot was then melted at a current of 220A. After each melting of the alloy ingot, the ingot was flipped and remelted. The melting was repeated 6 times to obtain the initial Ti-Ni-Sn alloy ingot.

[0053] (2) Homogenization heat treatment.

[0054] First, the Ti-Ni-Sn alloy ingot was cut into blocks with a height of 5mm using wire electrical discharge machining. The ingot surface was then cleaned with acetone solution in an ultrasonic cleaner for 3 minutes to remove oil stains. After removal, it was rinsed with alcohol and then dried completely with a cold air blower for 1 minute.

[0055] To prevent oxidation of the alloy ingot at high temperatures, it needs to be sealed in a vacuum-sealed quartz tube. The specific procedure is as follows: one end is sealed and the other end is open, with an inner diameter φ... ID =22mm, outer diameter φ OD A quartz tube with a diameter of 25mm and a length L0 of 250mm is prepared. The ingot to be homogenized by heat treatment is placed at one end of the sealed quartz tube, and a quartz plug is inserted for later sealing. First, a vacuum pump is used to evacuate the vacuum inside the quartz tube to <10. -6 After passing through Pa, high-purity argon gas (99.999%) is introduced for purging, and then the vacuum level inside the quartz tube is evacuated to <10. -6 Pa. A vacuum pump continuously evacuates air to maintain a constant vacuum level inside the quartz tube. A flame gun is used to heat the quartz stopper while the quartz tube is rotated to ensure uniform heating of the stopper. After melting, cooling, and solidifying, the quartz tube and stopper bond together, maintaining a high vacuum on the side where the alloy ingot is placed.

[0056] Subsequently, a homogenization heat treatment was performed by holding the tube at 1000℃ for 24 hours. After the heat treatment was completed, the quartz tube was quickly placed in water and the glass tube was broken, followed by room temperature water quenching.

[0057] (3) Room temperature cold rolling.

[0058] The homogenized heat-treated ingot is cold-rolled at room temperature (25°C) using a cold rolling mill. The deformation amount per pass is 1%, and no annealing is performed during the rolling process. Due to the springback of the material, when the roll pressure reaches the target deformation amount, the reduction in material thickness is less than the roll pressure, so rolling should continue. After each rolling pass, the material thickness is measured using vernier calipers until the ingot thickness reduction reaches 30%.

[0059] (4) Low-temperature annealing.

[0060] The cold-rolled and deformed ingot was sealed with a tube (same as in step (2)). The heat treatment process involved first heating the heat treatment furnace to 400°C, and then placing the sealed quartz tube into the furnace and holding it for 30 minutes. After the heat treatment was completed, the quartz tube was quickly placed in water and the glass tube was broken. The tube was then quenched at room temperature to obtain a low-temperature superelastic Ti-Ni-Sn shape memory alloy.

[0061] Example 1 Step (2) Homogenization of Ti after heat treatment 49.8-x-y Ni 50.2+x Sn y The secondary electron microstructure of the alloy (x = 0.1, y = 2) is shown in the figure below. Figure 1 As shown, the grain size of the alloy is approximately 10-20 μm.

[0062] Example 1 Step (2) Homogenization of Ti after heat treatment 49.8-x-y Ni 50.2+x Sn y The room temperature XRD pattern of the alloy (x = 0.1, y = 2) is shown below. Figure 2 As shown, the alloys prepared at room temperature are all composed of austenitic parent phase, and no obvious martensite phase or second phase diffraction peaks are observed.

[0063] Example 1 Step (2) Homogenization of Ti after heat treatment 49.8-x-y Ni 50.2+x Sn y The differential scanning calorimetry (DSC) plot of the alloy (x = 0.1, y = 2) is shown below. Figure 3As shown in the figure, there are two exothermic peaks during the cooling process. Peak1 corresponds to the transformation from the austenite parent phase to the R phase (called the R phase transformation), and Peak2 corresponds to the transformation from the R phase to the martensite phase (called the martensitic phase transformation). During the heating process, there is only one endothermic peak, Peak3, which corresponds to the transformation from the martensite phase to the austenite phase. Figure 3 The characteristic temperature of the alloy phase transformation, R, can also be obtained. s R f M s M f A s A f The K values ​​are 189K, 174K, 136K, 121K, 159K, and 196K, respectively, compared to commercially available TiNi alloys with the same atomic ratio (A s and A f The Ti prepared in this invention has K and K values ​​of 337K and 362K respectively. 49.8-x-y Ni 50.2+x Sn y (x=0.1,y=2) alloy A s Point and A f The K values ​​were reduced by 178 K and 166 K, respectively. This demonstrates that the comprehensive regulation of Sn element addition, content control, and substitution element selection enabled the TiNi alloy to achieve an extremely low phase transformation temperature, ensuring the material's superelastic properties at low temperatures.

[0064] In Examples 1-2, the Ti after step (3) cold rolling treatment + step (4) low-temperature annealing treatment 49.8-x-y Ni 50.2+x Sn y The differential scanning calorimetry (DSC) curve of the alloy (x = 0.1, y = 2) is shown below. Figure 4 As shown, similar to the alloy after homogenization heat treatment, two exothermic peaks, Peak1 and Peak2, exist during the cooling process, and the phase transformation temperature remains essentially unchanged. However, the peak intensity of Peak2 is significantly reduced, indicating that the thermally induced martensitic transformation of the alloy is strongly suppressed after cold rolling combined with low-temperature annealing. Simultaneously, no obvious endothermic peaks were found on the heating curve, indicating that the thermally induced reverse martensitic transformation of the alloy is also strongly suppressed; the temperature field alone cannot induce the reverse martensitic transformation.

[0065] Example 1: Ti after step (3) cold rolling treatment + step (4) low temperature annealing treatment 49.8-x-y Ni 50.2+x Sn y The tensile stress-strain curve of the alloy (x = 0.1, y = 2) is shown below. Figure 5 As shown, where ε re(SE) ε represents the residual strain of the alloy after unloading. re(SE)The figure shows the final residual strain of the alloy after heating to 80℃ and holding for 5 minutes. It can be seen that the alloy recovered some of its deformation after heating, indicating that shape memory effect exists simultaneously with hyperelastic deformation. As shown in the figure, the hyperelastic recovery rate of the material at -80℃ is 91.5%, the recoverable strain is 5.49%, and the unit damping energy is 770.0 J·m. -3 The material exhibits a hyperelastic recovery rate of 92.6% at -60℃, a recoverable strain of 4.63%, and a unit damping energy of 498.6 J·m. -3 .

[0066] Example 2: Ti after step (3) cold rolling treatment + step (4) low temperature annealing treatment 49.8-x-y Ni 50.2+x Sn y The tensile stress-strain curve of the alloy (x = 0.1, y = 2) is shown below. Figure 6 As shown, where ε re(SE) ε represents the residual strain of the alloy after unloading. re(SE) This represents the final residual strain after the alloy is heated to 80℃ and held for 5 minutes. At -80℃, the material's hyperelastic recovery rate is 91.2%, the hyperelastic recoverable strain is 5.47%, and the unit damping energy is 780.4 J·m. -3 The material exhibits a superelastic recovery rate of 87.0% at -60℃, a superelastic recoverable strain of 5.2%, and a unit damping energy of 804.5 J·m. -3 .

[0067] In summary, Ti 49.8-x-y Ni 50.2+x Sn y The alloy (x = 0.1, y = 2) still exhibits excellent superelastic properties at -80℃, with a large hysteresis loop area (500–800 J·m²). -3 Its high recoverability (>87%) makes it suitable for repeatable buffering in cryogenic environments, such as energy absorption during repeated landings of planetary probes.

[0068] The above description is merely a preferred embodiment of the present invention. These specific embodiments are different implementations based on the overall concept of the present invention, and the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a low-temperature superelastic Ti-Ni-Sn shape memory alloy, characterized in that, The low-temperature superelastic Ti-Ni-Sn shape memory alloy has the chemical formula Ti. 49.8-x-y Ni 50.2+x Sn y , where x = 0~0.4, y = 1.5~2.5; The preparation method of the shape memory alloy is carried out according to the following steps: (1) Smelting: Alloy ingots are prepared by vacuum arc melting according to the alloy composition; (2) Homogenization heat treatment: The alloy ingot is subjected to homogenization heat treatment under a sealed vacuum condition; (3) Room temperature cold rolling: The homogenized heat-treated ingot is cold rolled at room temperature; the deformation per pass is 1%, and the total deformation is 20-30%; (4) Low-temperature annealing: The cold-rolled ingot is subjected to low-temperature annealing at a temperature of 350-450℃ for 20-40 minutes to obtain a Ti-Ni-Sn shape memory alloy with low-temperature superelasticity.

2. The method according to claim 1, characterized in that, x=0.1, y=2.

3. The method according to claim 1, characterized in that, In step (2), the homogenization heat treatment is carried out at 1000-1050℃ for 24 hours.

4. The method according to claim 3, characterized in that, When y≤2, the homogenization heat treatment temperature is 1000℃, and when y>2, the homogenization heat treatment temperature is 1050℃.

5. The method according to claim 1, characterized in that, As y increases, the total deformation of cold rolling decreases.

6. The application of the shape memory alloy prepared by the method according to any one of claims 1-5 in the field of cryogenic deep space exploration.

7. The application according to claim 6, characterized in that, Low temperature refers to temperatures below -50°C.

Citation Information

Patent Citations

  • Low interstitial titanium-nickel-aluminum-vanadium shape memory alloy material for low temperature hyperelasticity

    CN103088234A

  • Super elastic ti-ni-al-cr alloy

    JP1988303022A

  • Nickel titanium alloys, methods of manufacture thereof and article comprising the same

    US20180179620A1